All-solid-state hybrid supercapacitors based on ZnCo2O4 nanowire arrays and carbon nanorod electrode materials. (October 2017) - Zhao, Jingxin; Li, Chaowei; Zhang, Qichong; Zhang, Jun; Wang, Xiaona; Sun, Juan; Wang, Juanjuan; Xie, Jixun; Lu, Conghua; Lu, Weibang; Yao, Yagang
Abstract: A high-performance, all-solid-state hybrid supercapacitor (HSC) device was assembled successfully. The ZnCo2 O4 nanowire array (NA)/carbon nanotube film (CNTF) positive electrode materials and the assembled device possess areal specific capacitances of 1.019 F cm −2 and 158.08 mF cm −2, respectively. A supernal volume energy density of 49.5 mWh cm −3 was obtained when the voltage window increased to 1.5 V. Moreover, the assembled HSC device exhibited good cycling stability with 90.7% initial capacitance retention after 6000 cycles, and the coulombic efficiency remained near 100%. Graphical abstract: The assembled all-solid-state asymmetric supercapacitor device possess excellent cycle stability and supernal volume energy density.